Socialization And Education About Industrial Waste At Cv Jamu Jaya Abadi Medan - Amenda Paswida Sebayang; Yudi Harjono Manik; Sarifah Hanum Chaniago; Wira Pratama Zega (Outline Publisher, 2024)
Indonesia is an agricultural country where various kinds of plants grow well. Some of these plants have the function of curing certain diseases in humans. Then people process these plants into herbal medicine. Jamu is made from a mixture of the juices of various plants which are useful for curing diseases. As an industry, CV exists. Jamu Abadi Jaya must be equipped with waste processing that allows the industrial activities carried out to remain environmentally friendly. The connection with this research is the waste water treatment installation which is related to waste water produced in industrial activities. The aim of this activity is to increase employee knowledge at CV Jamu Jaya Abadi Medan regarding handling industrial waste. This service activity was carried out by CV. Jamu Jaya Abadi Medan which is located at Ruko Spring Ville No.12, Jl. Bunga Rinte Simpang Selayang. Through education regarding waste management in the herbal medicine industry, there has been an increase in the knowledge of all employees. Increasing knowledge regarding waste management in the herbal medicine industry may be followed by processing residual waste from herbal medicine production. Nutrition education using the lecture method accompanied by leaflet media is one learning approach that provides a set of knowledge and skills needed to be able to determine the right behavioral choices to improve waste management in the herbal medicine industry at CV. Jamu Jaya Abadi Medan.